2017
DOI: 10.1186/s12865-017-0223-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reliable reference genes for the normalisation of gene expression levels following time course LPS stimulation of murine bone marrow derived macrophages

Abstract: BackgroundMacrophages are key players in the initiation, perpetuation and regulation of both innate and adaptive immune responses. They largely perform these roles through modulation of the expression of genes, especially those encoding cytokines. Murine bone marrow derived macrophages (BMDMs) are commonly used as a model macrophage population for the study of immune responses to pro-inflammatory stimuli, notably lipopolysaccharide (LPS), which may be pertinent to the human situation. Evaluation of the tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Among the putative macrophage clusters with elevated expression of macrophage-specific marker genes, including CD14 and CD68 (Khazen et al, 2005), we found a comparatively rare cluster of macrophages defined by the marker genes CD74 , HLA-DRA , B2M , and JUNB (AUROC > 0.90; Methods ) ( Figure 6 ). We hypothesized that this cluster corresponds to inflammatory macrophages, since each of its marker genes has been implicated in macrophage activation in response to inflammatory stimuli: CD74 encodes the receptor for macrophage migration inhibitory factor (MIF) (Leng et al, 2003), a pro-inflammatory signal (Morand et al, 2006; Santos and Morand, 2009); HLA-DR has elevated expression in classically pro-inflammatory M1-macrophages (Helm et al, 2014); increased B2M has been demonstrated in murine bone marrow derived macrophages after LPS stimulation (Tanaka et al, 2017); and JUNB has been implicated as a key transcriptional modulator of macrophage activation (Fontana et al, 2015) and is upregulated by MIF (Calandra and Roger, 2003). We did not observe major differences in the number of unique genes between this rare cluster and the rest of the macrophages ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the putative macrophage clusters with elevated expression of macrophage-specific marker genes, including CD14 and CD68 (Khazen et al, 2005), we found a comparatively rare cluster of macrophages defined by the marker genes CD74 , HLA-DRA , B2M , and JUNB (AUROC > 0.90; Methods ) ( Figure 6 ). We hypothesized that this cluster corresponds to inflammatory macrophages, since each of its marker genes has been implicated in macrophage activation in response to inflammatory stimuli: CD74 encodes the receptor for macrophage migration inhibitory factor (MIF) (Leng et al, 2003), a pro-inflammatory signal (Morand et al, 2006; Santos and Morand, 2009); HLA-DR has elevated expression in classically pro-inflammatory M1-macrophages (Helm et al, 2014); increased B2M has been demonstrated in murine bone marrow derived macrophages after LPS stimulation (Tanaka et al, 2017); and JUNB has been implicated as a key transcriptional modulator of macrophage activation (Fontana et al, 2015) and is upregulated by MIF (Calandra and Roger, 2003). We did not observe major differences in the number of unique genes between this rare cluster and the rest of the macrophages ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report using LPS stimuli in 6 hours cultured macrophages indicated the HNRNPAB as the most stable reference gene [18]. Two other studies reported ACTB as a reference gene in monocytes from septic patients [11,13].…”
Section: Discussionmentioning
confidence: 95%
“…Only few studies reported results of gene expression in monocytes/macrophages in sepsis experimental approaches ( Table 1). The authors mostly performed in vitro studies using mice bone marrow-derived monocytes/macrophages [18,22], J774A1 murine macrophage cell line [23], monocytes from healthy donors stimulated with LPS [24] and monocytes from patients with relapsing-remitting multiple sclerosis [25]. It is notable the lack of study in monocytes/macrophages from septic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-12 and its family member IL-23 (22,23) were also consistently and significantly increased by AZD5153 (Figure 2A). In order to validate the stability of gene expression under the experimental conditions in this study (24), we used three different normalizers and finally ascertained the results definitely ( Supplementary Figure 3). We further verified the concentration of IL-10 and IL-12 in the supernatant of macrophages by ELISA and found that the ratio of IL-10/IL-12 was significantly reversed in AZD5153-treated supernatant compared with one of M2-like macrophages (Figure 2B).…”
Section: Azd5153 Depolarized the Pro-tumor Phenotype Of Macrophage Inmentioning
confidence: 99%